Forensic perspectives on cybercrime: human behaviour and cybersecurity - McAlaney, John (New frontiers in forensic psychology, 2024)
"Forensic Perspectives on Cybercrime is the first book to combine the disciplines of cyberpsychology and forensic psychology, helping to define this emergent area. It explores the psychological factors that influence the behaviour of all those involved in cybersecurity, drawing upon the research literatures in relevant areas including forensic, social, and cyberpsychology. This unique text is a must-read for students undertaking any degree that relates to behaviour and cybersecurity, including psychology, computing, law and business management. It is also highly relevant to researchers, practitioners, and policymakers who work in cybersecurity have an interest in empowering people to be safe online"--